Simulation of a MEMS piezoelectric energy harvester - Md Ralib @ Md Raghib, Aliza 'Aini; Nordin, Anis Nurashikin; Salleh, Hanim (2010)
The growing demand of portable electronic devices has created the demand of long lasting recharged source of power. Non-environmental friendly conventional batteries with limited lifetimes are no longer a feasible option. This paper proposes a piezoelectric, vibration based energy harvester. The design and simulation of a MEMS piezoelectric cantilever beam with interdigitated electrodes is described. The micro-energy harvester is formed using a silicon substrate, ZnO piezoelectric layer, Pt electrodes and nickel proof mass. Finite element simulation was conducted using CoventorWare #x00A9; to obtain the device at resonance frequency, output voltage and optimum dimensions.